ChemInform Abstract: FeCl3·6H2O, a Catalyst for the Diastereoselective Synthesis of cis‐Isoxazolidines from N‐Protected δ‐Hydroxylamino Allylic Acetates. Issue 12 (25th March 2014) - Cornil, Johan; Guerinot, Amandine; Reymond, Sebastien; Cossy, Janine
Abstract It is found that FeCl3·6H2O effectively promotes eco‐friendly and diastereoselective access to cis‐3, 5‐disubstituted isoxazolidines.